Response of Growing Broiler to Varying Dietary Plant Protein - Ojewola, G.S.; Ewa, U.E. (International Journal of Poultry Science, 2005)
A five-week study was conducted to evaluate the productive performance, apparent nutrient utilization, carcass and organ proportion and economics of production of broilers fed five different plant proteins. Diet 1 contained 30% soyabean meal (SBM) while Diets 2,3, 4 and 5 contained pigeon pea seed meal (PPSM), groundnut cake (GNC), cashew nut meal (CNM) and cotton seed meal (CSM) respectively. One hundred and fifty-3-week old unsexed anak broilers were randomly allotted to the 5 dietary treatments in a completely randomized experiment (CRD). Each dietary group had 30 birds with 10 birds per replicate. Birds fed D5 has the highest mean daily intake (161.31g) that was significantly (P< 0.05) different from others while D1 gave the best feed-to-gain ratio (2.30) which is closely followed by D3 and D4 respectively. Birds fed D3 and 4 gave the best nutrient utilization. Calcium and phosphorous retained showed that D3 (66.41; 66.37) and D4 (59.94; 63.52) respectively gave better performance than others. Birds fed D4 gave the least (P< 0.05) mean total feed intake/bird (N) (217.13). It also had the highest net gain/bird (N332.87) which was significantly (P< 0.05) different from D1 (N 275.37) and D3 (N285.96), while other diets can be said to be comparable. The percent carcass yield ranged from 68.68 (D2) to 73.48 (D1) showing that high live weights lead to high dressed weights. In conclusion, cashew nut meal enhanced productive performance, carcass yield and economics of production while others are comparable.